2009
DOI: 10.1002/rem.20232
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and monitoring tools for aerobic bioremediation of vinyl chloride in groundwater

Abstract: Direct aerobic biodegradation of vinyl chloride (VC) offers a remedial solution for persistent vinyl chloride plumes that are not amenable to the anaerobic process of reductive dechlorination because of either prevailing geochemical conditions or the absence of active Dehalococcoidesethenogenes. However, tools are needed to evaluate and optimize aerobic VC bioremediation. This article describes the development and testing of two techniques-a microbiological tool and a molecular tool-for this purpose. Both met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…The PCR modifications employed in this study (nested and touchdown PCR) successfully amplified EaCoMT genes from environmental samples, but the results should be interpreted carefully with respect to PCR bias. The F131/R562 primers used in nested PCR were developed with etnE sequences from VC-assimilating Mycobacterium isolates (47) and are less degenerate than the CoMF1L/R2E primers, which were based on EaCoMT sequences from Mycobacterium sp. strain JS60, Gordonia B-276, and Xanthobacter Py2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PCR modifications employed in this study (nested and touchdown PCR) successfully amplified EaCoMT genes from environmental samples, but the results should be interpreted carefully with respect to PCR bias. The F131/R562 primers used in nested PCR were developed with etnE sequences from VC-assimilating Mycobacterium isolates (47) and are less degenerate than the CoMF1L/R2E primers, which were based on EaCoMT sequences from Mycobacterium sp. strain JS60, Gordonia B-276, and Xanthobacter Py2.…”
Section: Discussionmentioning
confidence: 99%
“…The first round of PCR utilized the CoMF1L and CoMR2E primer set (0.2 M each; see Table S2 in the supplemental material) as described previously (36) and 1 l of DNA extract (containing 0.14 to 15.7 ng template) ( Table 1). A subsequent round of nested PCR was performed with F131 and R562 primers (0.2 M each; see Table S2 in the supplemental material) (47) The potential that nested and touchdown PCR could introduce lower apparent gene diversity was investigated by constructing a pooled sample of DNA (referred to as AUS39) extracted from five different monitoring wells at the Australia site (i.e., samples 39-1, 39-3, 39-6, 39-7, and 39-8). DNA from AUS39 was amplified with three methods: conventional PCR, nested PCR, and a combined touchdown PCR-nested PCR.…”
Section: Methodsmentioning
confidence: 99%
“…The site was contaminated by disposal of material containing PCE at a landfill in 1986, which ultimately resulted in a large, dilute VC plume. Remediation efforts for the plume have involved oxygen and ethene injections and have been described previously (Begley et al 2009(Begley et al , 2012Chuang et al 2010;. The groundwater from these wells was composited; 1 L was shipped to the University of Iowa, where it was stored at 4°C in the dark.…”
Section: Site Information and Groundwater Collectionmentioning
confidence: 99%
“…Our initial microcosm studies demonstrated ethene‐stimulated VC‐metabolizing activity in mixed site groundwater. We also used a semiquantitative whole‐cell PCR assay (Begley et al 2009) to detect the presence of the epoxyalkane coenzyme M transferase gene, EaCoMT, which has been implicated in aerobic growth on both ethene and VC (Coleman and Spain 2003). The PCR test was applied to groundwater samples obtained from the site in June of 2007 and 2008, as previously reported (Begley et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…We also used a semiquantitative whole‐cell PCR assay (Begley et al 2009) to detect the presence of the epoxyalkane coenzyme M transferase gene, EaCoMT, which has been implicated in aerobic growth on both ethene and VC (Coleman and Spain 2003). The PCR test was applied to groundwater samples obtained from the site in June of 2007 and 2008, as previously reported (Begley et al 2009). EaCoMT positive colonies were found in each well, with wells undergoing active treatment having higher numbers of positive colonies, consistent with microcosm and biomass results.…”
Section: Resultsmentioning
confidence: 99%